A long way to go: gender and diversity in land use science. Issue 1 (2nd January 2022) - Kamau, Hannah N.; Tran, Uyen; Biber-Freudenberger, Lisa
ABSTRACT: Female scientists and researchers with diverse cultural backgrounds, especially of the Global South, are underrepresented in scientific systems. This is also the case for land use science and even for research teams researching in Global South countries. To assess trends in gender parity, ethnic diversity and intersectionality in this field, we conducted a meta-analysis based on systematic literature review that included 316, 390 peer-reviewed journal articles. We found that 27% of all authors between 2000–2021 represented women. Ethnicity representation was biased towards White researchers (62%) followed by Asian (30%), Hispanic (6%) and Black (2%) researchers. Intersection of inequalities further underrepresented Black and Hispanic women when author positions were considered, giving Black women 0.6% chance of becoming first authors in land use science in comparison to 19.3% chance of White women. Supportive actions to empower women are needed to reduce intersectional inequalities and to achieve the sustainable development goals.